Distributive outcomes matter: Measuring social preferences for climate policy - Lea Skræp Svenningsen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2017)
This study examines whether people have distributional preferences for the impacts of climate policy when making donations towards such policies. In an online choice experiment, using a real donation mechanism, a representative sample of 95 members of the Danish public are provided 27 exteuro and asked to make 16 donation choices among different climate policy options. The climate policies are described in terms of two main outcome variables, including future effects on income in 2100 and present co-benefits from mitigation action. Both outcomes are described for three specific regions of the world, Western Europe, Southeast Asia and Sub-Saharan Africa. For each participant, one policy choice was drawn at random to be realised and the total amount donated by participants was used to purchase and withdraw CO2 quotas and credits in the European Emission Trading Scheme and as a donation to the UN Adaptation Fund. A random parameter logit model shows that distributional concerns matter for people when they donate to climate policy and that elements of both inequity aversion and general altruism influence the choice of climate policy. The results underscore the importance of considering preferences for distributional outcomes when designing climate policy.
Keywords: D30; D91; Q51; Q54; Q58; 330; choice experiment; climate change; inequity aversion; altruism; random parameters logit; intergenerational; distributional social preferences